Clinicopathological spectrum of testicular lesions over a five-year period in a tertiary hospital - Sohaila Fatima; Rabab Nasir Mohamed Badri; Wajih Ahmed Siddiqui; Nihal Ibrahim Mirza (Tropical Journal of Pathology and Microbiology, 2019)
Objectives: To study the clinical pattern and histopathological features of testicular biopsies and orchiectomy specimens in patients presenting to a tertiary hospital.Methods: A 5 year retrospective study was conducted in histopathology section of Department of Laboratory Medicine, ACH from January 2014 to December 2018 on testicular tissue specimens (biopsies and orchiectomies). The histopathological diagnosis was made based on light microscopy followed by special stains and immunohistochemistry wherever indicated.Results: A total of 91 specimens were received in ACH during this 5 year period. The specimens comprised of cryptorchidism (16 cases), trauma (5 cases) , vascular lesions-testicular torsion (17 cases), inflammatory lesions (11 cases), Sertoli cell only syndrome (2 cases), spermatogenic arrest (3 cases), atrophy (3 cases), obstructive causes leading to infertility (3 cases), cyst (2 cases) , tumors (28 cases) and 1 was unremarkable .Inflammatory lesions were predominantly abscess (6 cases ), granulomatous orchitis (5 cases ).Tumors were classified into germ cell tumors –seminomas (10 cases), mixed germ cell tumors (9 cases) , teratomas (3 cases), embryonal carcinoma (2 cases), spermatocytic tumors (3 cases), Leydig cell tumor (1 case).Conclusions: The present study revealed that testicular masses were predominantly neoplastic mostly malignant primarily seen in age group 21-30 years with seminomas constituting 35.7 % of all tumors. Testicular torsion leading to ischemic necrosis were also seen in a large number of cases. Testicular biopsies might help in determining etiology of infertility which could be cryptorchidism, spermatogenic arrest, Sertoli cell only syndrome, atrophy and post testicular obstruction.